Analysing the factors that affect the adoption of payments bank services in India: an analytic hierarchy process approach. (29th July 2021) - Gupta, Kriti Priya; Manrai, Rishi; Goel, Utkarsh
Mobile financial services (MFS) provide added convenience to existing bank customers in developed markets, and act as a vehicle to achieve financial inclusion in developing countries. The Government of India launched a new MFS, i.e., payments banks (PB) with an objective of increasing the penetration level of banking services in the country. The purpose of the current study is to identify the most significant factors which influence the Indian customers to adopt PBS. The paper by carrying out literature review first identifies the factors which effect the customers' adoption of PBS and then using analytic hierarchy process (AHP) tries to prioritise them based on their relative importance. AHP was applied on the data and the results obtained reveal that 'perceived benefits' are of utmost importance for the adoption of payments banks services. Moreover, 'monetary benefits', 'time saving', 'trust in service provider', and 'financial risk', are the topmost four sub-factors for the enabling effective adoption of PBS.